Antimicrobial activity of Acacia nilotica (L.) Del. plant extracts against Xanthomonas malvacearum bacteria - Fatima, Sumia; Baig, Mirza Razia; Baig, Mumtaz; Kadam, V B (International Multidisciplinary Research Journal, 2012)
An experiment was conducted to check antibacterial activity of leaf bark and root extracts of Acacia nilotica (L.) Del. Plant against Xanthomonas malvacearum bacteria using agar well diffusion method expressed by zone of inhibition in mm in diameter. Antimicrobial activity of leaf, bark, and root extracts were separately assessed in triplicates for aqueous extracts, ethyl alcohol extracts. The results were compared with standard concentrations of antibiotics streptomycin and tetracycline. The ethyl acetate extracts of root seems to contain antibacterial component more than pure antibiotic with the concentration of 500 ug /ml.